LIFE CYCLE ASSESSMENT IMPLEMENTATION IN THE PACKAGING SECTOR FOR POLYMER AND BIOPOLYMER MATERIALS – A REVIEW - Šuput, Danijela; Popović, Senka; Ugarković, Jovana; Hromiš, Nevena (Journal on Processing and Energy in Agriculture, 2022)
Among many important requirements for packaging materials, environmental friendliness is property that has become necessary for any material that needs be competitive in the market. Life Cycle Analysis (LCA) is an analytical instrument that provides a framework for analyzing the impact of products and services on the environment, i.e. provides an understanding and the possibility of comparing different products. LCA studies the use of resources and the consequent emissions of pollutants on the environment during the entire life of a product from the raw materials exploitation, through production, use and treatment at the end of the life cycle - recycling and final disposal. This paper will provide an overview of the results of LCA analyzes of various commercial polymer packaging materials, as well as the results of LCA analyzes for biopolymer materials. Although LCA faces the problem of data heterogeneity, since some studies focused on individual segments of the analysis, while some related to all aspects of the process, as well with the problem of interpreting heterogeneous results, because the output parameters were arbitrarily selected by the researcher, still it could be concluded that the available LCA studies and environmental assessments support further development of biobased polymers. When comparing biopolymer materials with commercial synthetic polymers, they have advantages - lower consumption of fossil fuels and lower emission rate of greenhouse gases from the whole life cycle.
Keywords: life cycle, packaging, polymers, bioplymers